PENGARUH PENGGUNAAN SELEBRITI AGNES MONICA TERHADAP MINAT BELI KONSUMEN (STUDI KASUS: NEW ERA, PROVIDER 3, HONDA VARIO, CHITATO, DAN SHAMPO ZINC) - Debby Arthur Harris (Universitas Bunda Mulia, 2017)
This research aims to determine the influence of celebrity attractiveness (X1), celebrity credibility (X2), the fit between the celebrity and the product category (X3), and advertising weight (X4) on consumer purchase intention (Y). It is based on five brands as case studies: New Era shoe, 3 telco provider, Honda Vario motorcycle, Chitato snack, and Zinc shampoo. F test showed that the simultaneous influence of the independent variables was statistically significant. Meanwhile, t test found that celebrity attractiveness (X1) influence on purchase intention (Y) was significant only for Provider 3 case, whereas the other 3 independent variables had significant influence in all cases.Thus, in choosing celebrity endorser, advertisers are advised to consider the fit between the celebrity and the product category, advertising weight, and celebrity credibility. Keywords : Celebrity endorser, Advertising